Compreensão do adoecimento psíquico : de L. S. Vigotski à patopsicologia experimental de Bluma V. Zeigarnik - Silva, Maria Aparecida Santiago da (2014)
This dissertation is the result of literature review, of theoretical-conceptual nature, linked to the Postgraduate Program in Psychology at the State University of Maringá (2012-2014) in the research field Constitution of the Subject and Historicity and the search line Educational Processes and Social Practices. It aims to study the mental disorder from the theoretical and methodological principles of Historical-Cultural Psychology, specifically the L. S. Vigotski and the Experimental Abnormal Psychology of Bluma V. Zeigarnik, psychological discipline which is still quite unknown in Brazil. The study starts by a historic retreat on the relationship between the scientific field of psychiatry and psychology in Russia and the Soviet Union, to understand how the vigotskian psychology - whose philosophical and epistemological base is based on the historical and dialectical materialism ? which explains certain mental disorders, treated, predominantly, in the context of psychiatry. The political and economic factors have impacted the sciences in general from the Soviet social transformations and also have influenced the Psychology, which was uncharacteristic of its subject, the man, including the mentally ill. This was due to the value assigned to the physiology and psychiatry, with some inserts in that field made by Vigotski in the 1930s, which were the basis for Zeigarnik's work after the 1960s. The next two steps of the research are interconnected, since they discuss the assumptions from the Historical-Cultural Psychology, governing the understanding of the mental illness in this methodological bias. Thus, in the second chapter the contributions of Vygotsky are presented in the explanation of human development and the processes of disintegration of psychological processes, especially in the studies about the schizophrenia. These works were the base for the investigation of the pathological changes of mental activity by the Experimental Abnormal Psychology, focusing, more specifically, the contribution of Leontiev's Activity Theory, as explained in the third chapter. To Zeigarnik, on the mental illness, there is the creation of pathological needs and the changing of the hierarchy of motives from a pathological behavior of human activity, which has its structure modified, leading to other psychological commitments, mainly regarding the personality of man. Starting from the understanding of human development as a process related to man's social and material life, the present study may contribute to the explanation of mental illness in pathogenic conditions of education and work tied to class relations and capitalist production in the current historical context. We hope to establish a solid base for action based on ethical and political commitment, attending to pathogenic social conditions, seeking ways to transform them into individual and collective work in the sphere of mental health, achieving explanations beyond the limited and ahistorical ones, but seeking multiple determinations of humans phenomena.